2023
DOI: 10.3390/socsci12040221
|View full text |Cite
|
Sign up to set email alerts
|

Value of Critical Thinking in the Labour Market: Variations in Employers’ and Employees’ Views

Abstract: The fragmentation and narrowness of research on critical thinking in the labour market and the lack of critical thinking analysis in the context of the interplay between lifelong learning, education and the labour market presuppose the relevance of this article. The article analyses the views of employers and employees, highlighting their attitude toward the importance and manifestation of critical thinking in the labour market and the need for improving critical thinking competency. The article aims to answer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These enabling skills are central to thinking on professional development and increasingly valued in the labour market (Indrasiene et al, 2023;CIPD, 2019). As we will see in the next section these capabilities are increasingly of value to Liam as he progresses in the business postmaster's.…”
Section: Learning Whilst Working: the Master'smentioning
confidence: 99%
“…These enabling skills are central to thinking on professional development and increasingly valued in the labour market (Indrasiene et al, 2023;CIPD, 2019). As we will see in the next section these capabilities are increasingly of value to Liam as he progresses in the business postmaster's.…”
Section: Learning Whilst Working: the Master'smentioning
confidence: 99%
“…Personal and structural characteristics influence the development of educational and occupational preferences, which in turn affect perceptions of the labour market (Dimaki et al, 2005). Indrašienė et al (2023) found that employers and employees have different perspectives on the value and application of critical thinking in the workplace, highlighting the need to enhance critical thinking skills. Firm characteristics, national locations, and sectoral associations all influence how firms perceive labour market constraints such as labour regulations and skill shortages (Fakih & Ghazalian, 2015).…”
Section: Introductionmentioning
confidence: 99%